1987
DOI: 10.1128/mcb.7.1.403
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Saccharomyces cerevisiae centromere DNA-binding protein, its human homolog, and its possible role as a transcription factor.

Abstract: A protein that binds specifically to Saccharomyces cerevisiae centromere DNA element I was purified on the basis of a nitrocellulose filter-binding assay. This protein, termed centromere-binding protein 1 (CP1), was heat stable and renaturable from sodium dodecyl sulfate (SDS), and assays of eluates from SDS gels indicated a molecular weight of 57,000 to 64,000. An activity with similar specificity and stability was detected in human lymphocyte extracts, and analysis in SDS gels revealed a molecular weight of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(120 citation statements)
references
References 45 publications
2
117
0
1
Order By: Relevance
“…We examined both palindromic CACGTG motifs and non-palindromic CACATG motifs. Motifs within the GAL2, GSH1, and SHU1 loci were chosen based on reports of Cbf1p-dependent changes in transcription (5,19,37,45). The remaining loci, DRS2, GDH3, PSK1, FUN30 and ERV46 (46 -50), were chosen at random from the left arm of chromosome I with the exception of GAL3 (51) on chromosome IV, which was chosen because it is associated with three CACATG motifs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined both palindromic CACGTG motifs and non-palindromic CACATG motifs. Motifs within the GAL2, GSH1, and SHU1 loci were chosen based on reports of Cbf1p-dependent changes in transcription (5,19,37,45). The remaining loci, DRS2, GDH3, PSK1, FUN30 and ERV46 (46 -50), were chosen at random from the left arm of chromosome I with the exception of GAL3 (51) on chromosome IV, which was chosen because it is associated with three CACATG motifs.…”
Section: Resultsmentioning
confidence: 99%
“…shown to bind to yeast centromere DNA (5)(6)(7)(8) via the CACRTG motif, which is found within the consensus centromere DNA Element 1 (CDEI) 1 RTCACRTG. Deletion of the CBF1 gene or deletion of CDEI motifs from centromeric DNA led to similar defects in mitotic and meiotic centromere function, indicating that Cbf1p is an important component of the centromerekinetochore complex (9,10).…”
mentioning
confidence: 99%
“…Deletion mutants placing the BGP Alu sequences or the two direct repeats in the upstream region immediately adjacent to the minimal promoter did not affect luciferase expression either, but the effects of these elements may be position dependent. [53]; AP-2 (conl), AP-2 consensus sequence 1 [53]; AP-2 (con2), AP-2 consensus sequence 2 [64] ; GAL2, the USF site in the GAL2 gene [63]; USF consensus sequence 1401; 01-AT, the HNF-4/LF-A1 site in the al-antitrypsin gene [52]; HNF-4 consensus sequence [41]; LF-A1 consensus sequence [52].…”
Section: Activation Of the Bgp Promoter By Usf And Hnf-4 In Cotransfementioning
confidence: 99%
“…CDEII seems to be also necessary for optimal centromere activity but so far no protein has been reported that binds to CDEII. However, several proteins that bind to CDEI and CDEIII have been identified (Bram and Kornberg, 1987;Baker et al, 1989;Cai and Davis, 1990;Lechner and Carbon, 1991). These proteins are named centromere-binding factors (Cbf) and assemble into a centromere complex.…”
Section: Introductionmentioning
confidence: 99%
“…Cbf1 is a helix-loop-helix leucine zipper protein that binds as a homodimer directly to the CDEI-DNA element of the centromere (Bram and Kornberg, 1987;Baker et al, 1989;Mellor et al, 1990). Functional studies in haploid S. cerevisiae cells showed that Cbf1p is non-essential (Cai and Davis, 1990).…”
Section: Introductionmentioning
confidence: 99%